2011
DOI: 10.1063/1.3598424
|View full text |Cite
|
Sign up to set email alerts
|

Spin-spin correlation functions of the q-valence-bond-solid state of an integer spin model

Abstract: We consider the valence-bond-solid ground state of the q-deformed higher-spin AKLT model (q-VBS state) with q real. We investigate the eigenvalues and eigenvectors of a matrix (G matrix), which is constructed from the matrix product representation of the q-VBS state. We compute the longitudinal and transverse spinspin correlation functions, and determine the correlation amplitudes and correlation lengths.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…On the other hand, we have already seen that the Bloch spin-coherent state enables us to relate the Laughlin-Haldane wave functions to the VBS states. In correspondence with such QHE, a variety of VBS models have been constructed with the symmetries, such as SO (5), SO(2n + 1) [107,108,109], SU (N + 1) [110,111,112,113], Sp(N ) [114,115], and q-deformed SU (2) [21,22,116,117,118] [see Fig. 2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we have already seen that the Bloch spin-coherent state enables us to relate the Laughlin-Haldane wave functions to the VBS states. In correspondence with such QHE, a variety of VBS models have been constructed with the symmetries, such as SO (5), SO(2n + 1) [107,108,109], SU (N + 1) [110,111,112,113], Sp(N ) [114,115], and q-deformed SU (2) [21,22,116,117,118] [see Fig. 2].…”
Section: Introductionmentioning
confidence: 99%
“…For(117), the order parameter ∆ k = c † k c † −k , the electron number n k = c † k c k , and its fluctuation δn k , are…”
mentioning
confidence: 99%
“…Recently Santos et al found surprisingly simple and useful formula for calculating the reduced density matrix for matrix product ground states [32,33]. They applied it to the AKLT model of spin-1 and general integer spin S with quantum group symmetry (q-AKLT model) [3,5,10,19,20,24,35], and another massive Klümper-Schadschneider-Zittartz model [21] to study anisotropic effect.…”
Section: Introductionmentioning
confidence: 99%
“…We obtain the expression of the geometric entanglement for → ∞ and its finite size corrections with help of numerical calculations. For the evaluation of the entanglement entropies and the geometric entanglement, the spectral structure of the transfer matrix of the q-VBS state in the matrix product representation [3,24] will be helpful. This article is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation